The Use of MALDI-TOF Mass Spectrometry to Analyze Commensal Oral Yeasts in Nursing Home Residents - Lu, Jang-Jih; Lo, Hsiu-Jung; Lee, Chih-Hua; Chen, Mei-Jun; Lin, Chih-Chao; Chen, Yin-Zhi; Tsai, Ming-Horng; Wang, Shao-Hung (Microorganisms, 2021)
Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) is a rapid and accurate method to identify microorganisms in clinical laboratories. This study isolates yeast-like microorganisms in the oral washes that are collected from non-bedridden nursing home residents, using CHROMagar Candida plates, and identifies them using Bruker MALDI-TOF MS. The ribosomal DNA sequences of the isolates are then examined. Three hundred and twenty yeast isolates are isolated from the oral washes. Candida species form the majority (78.1%), followed by Trichosporon/Cutaneotrichosporon species (8.8%). Bruker MALDI-TOF MS gives a high-level confidence, with a log(score) value of ≥1.8, and identifies 96.9% of the isolates. There are six inconclusive results (1.9%), and those sequences are verified as rare clinical species, including Candida ethanolica, Cutaneotrichosporon jirovecii, Exophiala dermatitidis, and Fereydounia khargensis. Almost all of the isolates have a regular color on the CHROMagar Candida plates. If the colonies are grouped by color on the plates, a specific dominant yeast species is present in each color group, except for purple or orange isolates. In conclusion, MALDI-TOF MS is verified as a fast, accurate and practical method to analyze oral yeasts in elderly subjects.